2019
DOI: 10.1016/j.celrep.2019.05.037
|View full text |Cite
|
Sign up to set email alerts
|

The Fat Mass and Obesity-Associated Protein (FTO) Regulates Locomotor Responses to Novelty via D2R Medium Spiny Neurons

Abstract: Graphical Abstract Highlights d FTO controls locomotor responses and exploration to novelty via striatal D2 MSNs d FTO regulates D2 MSN excitability and their external globus pallidus projections d Motor responses to dopaminergic activation is attenuated upon FTO loss in D2 MSNs d Mice lacking FTO in D2 MSNs are predisposed to directpathway activation SUMMARYVariations in the human FTO gene have been linked to obesity and altered connectivity of the dopaminergic neurocircuitry. Here, we report that fat mass an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…RNA extraction was performed by first homogenizing samples in 1 mL Trizol LS (Life Technologies) at 3000 rpm using estingly, with regard to neurological disease, sexual dimorphisms exist where, for example, in humans, male dominance is noted in cases of ADHD and female dominance is noted in overweight and obesity (1,58,59). Of note, we have recently shown that ablation of the obesity-associated FTO gene from postsynaptic DA neurons also manifests with increased locomotion in response to novelty in male but not female mice (60). Further research is necessary to understand how the maternal metabolic environment can result in sexually dimorphic outcomes based on the broad effects on brain development and function.…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction was performed by first homogenizing samples in 1 mL Trizol LS (Life Technologies) at 3000 rpm using estingly, with regard to neurological disease, sexual dimorphisms exist where, for example, in humans, male dominance is noted in cases of ADHD and female dominance is noted in overweight and obesity (1,58,59). Of note, we have recently shown that ablation of the obesity-associated FTO gene from postsynaptic DA neurons also manifests with increased locomotion in response to novelty in male but not female mice (60). Further research is necessary to understand how the maternal metabolic environment can result in sexually dimorphic outcomes based on the broad effects on brain development and function.…”
Section: Methodsmentioning
confidence: 99%
“…Variations in the FTO gene can not only regulate D2Rdependent reward learning [106][107][108], but also affect nerve adjust food visual, produce more frequent rewards [109][110][111], affect the control of mood and impulse [112][113][114], and affect obesity by regulating brain signaling pathways [115,116]. The homozygous mutation of FTO gene can reduce the brain capacity of healthy elderly people, increase the susceptibility to brain atrophy during aging, and even affect the brain volume of adolescents [117,118].…”
Section: Resultsmentioning
confidence: 99%
“…This biochemical modification has appealed to significant attention. The association of FTO gene variation and adiposity with increased body mass has been reported in many studies [14]. Fischer et al (2009) compared the reduction of adiposity and protection from induced diet obesity by the ubiquitous inactivation of Fto and increased body mass and fat with the overexpression of FTO in mice [15].…”
Section: Introductionmentioning
confidence: 94%